Pengaruh Kebijakan Program Gerakan Literasi Sekolah terhadap Minat Baca Peserta Didik SMA Al Huda Tuban - Atik Nihayatuzen; Fahrur Rosikh; Hidayatul Mufidah (Mudir : Jurnal Manajemen Pendidikan, 2021)
The climate of literacy in education is increasingly being voiced. To realize the National Literacy Movement, both in the realm of schools, families, and communities, a comprehensive and well-planned strategy is needed. Seeing the importance of reading culture and the lack of interest in reading in Indonesia, the government has launched a literacy movement. The implementation of this strategy is by creating the School Literacy Movement carried out by the Government in the field of education, namely the Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System. In Chapter III article 4 paragraph 5, it reads Education is carried out by developing a culture of reading, writing and arithmetic for all members of the community, making policies regarding reading interest. Interest in reading is expected to grow and develop in these students, guided by the policy of the school literacy movement or commonly referred to as GLS. Thus, it is hoped that schools will be able to develop government policies through literacy movement guidelines which will be able to be implemented and developed according to the situation and conditions of the school. This study discusses how the literacy movement policy in increasing students interest in reading at SMA Al-Huda Tuban. This research is a quantitative research. The research sample is class XI students totaling 47 students. Collecting data with the methods of observation, questionnaires, interviews, and documentation. Test the validity of the data by using the validity test and reliability test. Data analysis with descriptive analysis, hypothesis testing, Product moment analysis. The results of the study explain that there is a good implementation and strategy that leads to increasing students reading interest. The results showed: (1) The literacy movement policy at SMA Al-Huda Tuban was quite good. The number of respondents was the most among the grouping of scores from the number of respondents 47, which was obtained a score of 71-75 with 12 respondents. (2) Reading interest in high school Al-Huda Tuban has the highest frequency, namely 15 respondents with a mean value of 78.463 mode 80 and a median of 80. (3) School Literacy Movement Program on Student Interest in Reading at SMA Al-Huda Tuban, with rxy = 0.759 with a significance value of 0.566 or 0.56 percents.